2012
DOI: 10.1128/aem.00304-12
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Clostridium botulinum ATCC 3502 Sigma Factor K in Early-Stage Sporulation

Abstract: ABSTRACTA key survival mechanism ofClostridium botulinum, the notorious neurotoxic food pathogen, is the ability to form heat-resistant spores. While the genetic mechanisms of sporulation are well understood in the model organismBacillus subtilis, nothing is known about these mechanisms inC. botulinum.Using the Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 40 publications
3
46
0
Order By: Relevance
“…However, whether sigK expression peaks during mid-to late stationary phase in C. botulinum, as seen in C. acetobutylicum (21) and B. subtilis (65), is still unknown. Spore staining and microscopy analysis of the sigK mutant generated in C. botulinum ATCC 3052 showed that the mutant did not produce spores and that the cells exhibited an elongated phenotype (64). These images suggest that sporulation was blocked prior to stage II, as observed for the C. perfringens sigK mutant (63).…”
Section: K Is Activated Late In the Bacillus Model But Also Has A Surmentioning
confidence: 78%
See 3 more Smart Citations
“…However, whether sigK expression peaks during mid-to late stationary phase in C. botulinum, as seen in C. acetobutylicum (21) and B. subtilis (65), is still unknown. Spore staining and microscopy analysis of the sigK mutant generated in C. botulinum ATCC 3052 showed that the mutant did not produce spores and that the cells exhibited an elongated phenotype (64). These images suggest that sporulation was blocked prior to stage II, as observed for the C. perfringens sigK mutant (63).…”
Section: K Is Activated Late In the Bacillus Model But Also Has A Surmentioning
confidence: 78%
“…Surprisingly, disruption of sigK in C. difficile did not lead to the complete loss of sporulation, as 10 3 heat-resistant spores/ml were detected at 72 h (25,94). This finding is in stark contrast to the sigK mutants generated in B. subtilis, C. perfringens, C. botulinum, and C. acetobutylicum, all of which resulted in an asporogenous phenotype (37,63,64,66). TEM image analysis revealed that the C. difficile sigK mutant produced forespores with what appears to be a cortex layer, but no coat layer was observed (94) (Fig.…”
Section: K Has a Second Role Late In Sporulation As The Second Mothmentioning
confidence: 84%
See 2 more Smart Citations
“…The E protein in the C. perfringens sigK disruption mutant could not be detected by Western analysis, thus confirming that K is active upstream of E in the sporulation cascade (12). A sigK disruption mutant was also generated in Clostridium botulinum, and its sporulation was also blocked at an early stage (13). Quantitative reverse transcription-PCR (qRT-PCR) analysis on the wild-type (WT) C. botulinum strain revealed that sigK expression was downregulated during early stationary phase.…”
mentioning
confidence: 92%